Metode Guru dalam Membiasakan Santri Non-Jawa Menguasai Tulisan Pegon di Pondok Pesantren Al-Iman Bulus Purworejo - Naiela Sangadah; Tahrir Rosadi (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
This study examines the teacher’s methods in familiarizing non-Javanese students with the Pegon writing system at Pondok Pesantren Al-Iman Bulus, Purworejo. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The findings reveal that teachers employ three learning categories: formal (imlak, khot, tamrin, muthola’ah), non-formal (discussion, peer learning), and spiritual (ngaji ndalem). These methods help non-Javanese students gradually adapt to the linguistic and cultural environment of the pesantren. The study highlights that the integration of classical and practical teaching methods, combined with a spiritual learning atmosphere, strengthens students’ mastery of Pegon and fosters intercultural adaptation.